A single eye 3D image perception device using vertical double ring resonator construction - Saktioto, T.; Irawan, D.; Yupapin, Preecha P.; Phatharacorn, Prateep (My University, 2015)
A single eye three-dimensional (3D) imaging perception using a single 3D imaging pixel is designed and manipulated, which is the interesting device configuration that can be used for various applications. The device configuration is consisted of double conjugate mirrors that can be vertically fabricated, which can be used to form the 3D image using a single pixel configuration, from which the large area device construction is also possible. By adjusting the microconjugate mirror parameters, then the matching between both microconjugate mirrors can lead to obtain the required 3D images. Results obtained have shown that the 3D image outputs can be achieved and used for 3D pixel imaging. The 3D image output can be confirmed by the four-wave mixing output balancing profile, which is achieved. In applications, the large area 3D images can be constructed using the large area 3D imaging device, from which the large area can be coverage by the microconjugate mirror array, which can be useful for various applications.
Keywords: 3D imaging device; 3D pixel imaging; aritficial eye; microconjugate mirror; single eye on-chip